Self-efficacy in protecting oneself against HIV transmission: A qualitative study of female university students in Malawi - van Pelt, Inger Sofie; Ryen, Anne (Journal of Comparative Social Work, 2015)
This article deals with the complexity of health behaviour from a self-efficacy perspective, and shows the naivety in assuming knowledge as the main guide to better protection against HIV. The authors accentuate the importance of local knowledge when developing health strategies as in the case of protection against HIV, in this case for female university students in Malawi. Being part of a transition period, these students have to handle complex and at times opposing expectations. This makes HIV protection into a complex social- and health issue. However, the close association between universities and rational thinking has for long made public health see self-efficacy as one of the main determinants in general health behaviour. By seeing health behaviour as complex, this study explores into how female university students perceive their own self-efficacy in protecting themselves against HIV in Malawi with a HIV score of approximately 12%. The study is based on data from Chancellor College in Zomba, Malawi. The authors point to the potential of a closer collaboration between social work and public health in issues of both a social and a health nature, as in the case of HIV protection.